VINTGES, Karen. A New Dawn for the Second Sex: Women's Freedom Practices in World Perspective - Santos, Magda Guadalupe dos (Virtuajus, 2017)
Resenha do livro A New Dawn for the Second Sex. Women’s Freedom Practices in World Perspective (Amsterdam University Press, 2017), de Karen Vintges, Professora de Filosofia Política e Social do Departamento de Filosofia da Universidade de Amsterdam.